STUDENT’ANXIETY IN LEARNING SPEAKING - Yasti Januariza; Suswati Hendriani (Universitas Negeri Padang, 2016)
Speaking is one of the important skills that students should master. in order that they are able to deliver their ideas. To master the skill, the students, certainly, should have much practice, should be self-confident, not be nervous, no be anxious, must be brave, enjoy speaking. In reality, many students are too anxious and do not enjoy learning speaking. They try to finish speaking practices as soon as possible when they get turn to speak or be the last performer. They try to memorize all of materials before entering speaking classes to avoid making a mistake. Unfortunately, the lecturer who teaches Speaking subject, do not know the personality of his students very well. Thus, he forces the students who are not ready yet to speak up. Consequently, they lose their ideas or decide not to speak even when their lecture asks them to do it. Why are the students reluctant to speak was found through a qualitative research. The informants of the research are the students of English Teaching Department of State Institute for Islamic Studies (IAIN) Batusangkar. The technique of data collections are a open-ended questionnaire and in-depth interview. The results of the research show the causes of the students’ anxiety are: fear of mistake, fear of being laughed at or mocked, lack of ability, lack of preparation, lack of practice, lack of vocabulary, lack of self-confidence, lack of conviction, lack of motivation, shyness, not liking the speaking subject, the teacher’s teaching method, and the teachers’ attitude and behavior.